Increasing the Size of an Aromatic Helical Foldamer Cavity by Strand Intercalation1. Issue 48 (5th October 2014) - Singleton, Michael L.; Pirotte, Geert; Kauffmann, Brice; Ferrand, Yann; Huc, Ivan
Abstract The postsynthetic modulation of capsules based on helical aromatic oligoamide foldamers would be a powerful approach for controlling their receptor properties without altering the initial monomer sequences. With the goal of developing a method to increase the size of a cavity within a helix, a single‐helical foldamer capsule was synthesized with a wide‐diameter central segment that was designed to intercalate with a second shorter helical strand. Despite the formation of stable double‐helical homodimers (Kdim>107 M−1) by the shorter strand, when it was mixed with the single‐helical capsule sequence, a cross‐hybridized double helix was formed with Ka>105 M−1. This strategy makes it possible to direct the formation of double‐helical heterodimers. On the basis of solution‐ and solid‐state structural data, this intercalation resulted in an increase in the central‐cavity size to give a new interior volume of approximately 150 Å3.